Evaluation of critical conditions in offshore vessel operation by response based optimization procedures - Clauss, Günther F.; Klein, Marco; Sprenger, Florian; Testa, Daniel (29th International Conference on Ocean, Offshore and Arctic Engineering: Volume 4, 2010)
During the design process of floating structures, different boundary conditions have to be taken into account. Besides the basic determination of the type of vessel, the range of application and the main dimensions at the initial stage, the reliability and the warranty of economical efficiency are an inevitable integral part of the design process. Model tests to evaluate the characteristics and the performance of the floating structure are an important milestone within this process. Therefore it is necessary to determine an adequate test procedure which covers all essential areas of interest. The focus lies on the limiting criteria of the design such as maximum global loads, maximum relative motions between two or more vessels or maximum accelerations, at which the floating structure has to operate or to survive. These criteria are typically combined with a limiting characteristic sea state (Hs, Tp) or a rogue wave. However, the important question remains: What is the worst case scenario for each design parameter - the highest rogue wave or a wave group of certain frequency? And which sea states have to be taken into account for the experimental evaluation of the limiting criteria? As an approach to these challenges, a response based wave generation tool for critical wave sequence detection is introduced. By means of this procedure, model tests can be conducted more efficiently. Besides the theoretical background of the response based wave generation tool, an exemplary practical application for a multi-body system is shown with maximum relative motions as the limiting criterion.